Pengembangan Media Buku Cerita Digital Pada Pembelajaran IPS Materi Kerajaan Islam Kelas IV Sekolah Dasar - Sofian Abdulatif; Muh. Husen Arifin (Jurnal Elementaria Edukasia, 2023)
This research is the development of digital storybook media in social studies learning material on the Islamic kingdom in grade IV elementary school. This was done because of students' lack of interest in learning social studies in elementary schools. This research aims to design, test the feasibility and determine the response to digital storybook media in elementary schools. The method used in the research is Design and Development using the ADDIE model development which includes 5 stages, namely analysis, design, development, implementation and evaluation. Research participants consisted of material experts, linguistic experts, media experts as well as users, namely teachers and students, to obtain the results of the feasibility assessment of the learning media that had been created, as well as responses from users. The data analysis techniques used include data collection, data presentation, data reduction and drawing conclusions to answer the proposed problem formulation. Therefore, the digital storybook learning media was designed using Canva and ibispaintX as application platforms. Responses from material experts, media experts and language experts received very good responses and were worth testing with elementary school students. The response from student users and teachers received a positive response. From these responses, digital storybook media is suitable for use in learning and has received positive responses from students and teachers.